Metallization method of ceramic substrate and ceramic copper-clad substrate
By adding a TiN/Ti gradient transition layer between the ceramic substrate and the copper seed layer, the problems of poor interface bonding and high thermal resistance in the metallization method of silicon nitride ceramic substrate are solved, and a high-strength and heat-resistant ceramic copper clad substrate is realized.
Patent Information
- Application Number
- CN202510057583.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-14
AI Technical Summary
The existing metallization method for silicon nitride ceramic substrates has problems such as complex preparation process, large stress on the metal and ceramic interface leads to poor interface bonding, and high thermal resistance of the multi-layer interface will reduce heat dissipation performance.
By adding a TiN/Ti gradient transition layer between the ceramic substrate and the copper seed layer and controlling its thickness nano-normalization, a reliable connection between the silicon nitride ceramic substrate and the metal copper is achieved.
The interface bonding strength and cold and heat resistance of the silicon nitride ceramic copper clad substrate are greatly improved, which solves the problems of poor interface bonding and high thermal resistance, and improves the heat dissipation performance.
Smart Images

Figure CN119890050A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of silicon nitride ceramic metallization, and in particular to a ceramic substrate metallization method and a ceramic copper-clad substrate. Background Art
[0002] With the continuous development of lightweight and integrated high-power electronic devices, heat dissipation has become a key technology that affects device performance and life. In power modules, the heat dissipation substrate not only has to bear the functions of electrical connection and mechanical support, but is also an important heat dissipation channel. As a new type of heat dissipation material, ceramic substrate has excellent thermal conductivity, insulation, pressure resistance and good thermal matching with chips. It is widely used as a key material for IGBT modules in new energy vehicles, high-speed railways, LED lighting and other fields. The full English name of IGBT module is Insulated Gate Bipolar Transistor Modules, and its Chinese name is Insulated Gate Bipolar Transistor Module.
[0003] Before packaging the ceramic substrate, its surface must be metallized, that is, a metal conductive layer is firmly adhered to the ceramic surface to achieve the connection between ceramic and metal. Metallization is the most important link in the ceramic substrate manufacturing process, which determines the packaging performance, manufacturing cost and service life of the device. However, the inherent difference in thermal expansion coefficients between ceramics and metals causes large stresses to be generated at the interface between the two when the substrate is subjected to thermal cycles, resulting in ceramic cracking or metal layer peeling, which in turn leads to module failure. Therefore, how to implement metallization with high interface bonding strength and thermal shock resistance on the ceramic surface is a key issue to break through its application bottleneck.
[0004] Silicon nitride ceramic substrates have excellent comprehensive properties such as high thermal conductivity, high mechanical properties and high reliability, and have gradually become the most promising substrate material for high-power modules. After metallization, they can weld thicker oxygen-free copper and achieve higher reliability in IGBT modules for electric vehicles. However, at present, the thermal cycling resistance of silicon nitride ceramic copper-clad laminates cannot meet the requirements of electric vehicles to maintain performance after 3,000 thermal cycles at -40°C to 250°C. Therefore, the development of new silicon nitride ceramic surface metallization technology to provide strong interface bonding and high temperature impact resistance is the key to manufacturing high-reliability and high-quality silicon nitride ceramic substrates.
[0005] At present, the metallization methods of silicon nitride ceramic substrates mainly include direct copper coating and active metal brazing. Although the silicon nitride substrates processed by these methods have certain reliability, the existing metallization methods of silicon nitride ceramic substrates still have problems such as complex preparation process, large interface stress between metal and ceramic resulting in poor interface bonding, and high thermal resistance due to thick interface. Summary of the invention
[0006] In order to solve the problems of large metal-ceramic interface stress resulting in poor interface bonding and thick interface resulting in high thermal resistance in existing metallization methods of silicon nitride ceramic substrates, the present invention aims to provide a ceramic substrate metallization method and a ceramic copper-clad substrate.
[0007] To achieve the above objectives, the technical solution of the present invention is as follows.
[0008] A first aspect of the present invention provides a method for metallizing a ceramic substrate, comprising the following steps:
[0009] A TiN / Ti gradient transition layer and a Cu seed layer are sequentially deposited on the surface of a ceramic substrate by magnetron sputtering to prepare a ceramic copper-clad substrate; the TiN / Ti gradient transition layer comprises a TiN transition layer and a Ti transition layer; the thickness of the TiN transition layer is between 100nm and 600nm; the thickness of the Ti transition layer is between 100nm and 200nm.
[0010] The present invention realizes reliable connection between the silicon nitride ceramic substrate and the metal copper by adding a TiN / Ti gradient transition layer between the ceramic substrate and the copper seed layer and controlling the thickness of the TiN / Ti gradient transition layer to nanometer, thereby greatly improving the interface bonding strength and thermal cycling resistance of the silicon nitride ceramic copper-clad substrate, so as to solve the problems that the existing metallization method of the silicon nitride ceramic substrate still has the problems of complex preparation process, large interface stress between the metal and ceramic resulting in poor interface bonding, and high thermal resistance of the multi-layer interface reducing the heat dissipation performance.
[0011] Preferably, the TiN transition layer has at least one layer, and the thickness of each TiN transition layer is 100nm to 200nm. The present invention solves the problem of interface bonding between silicon nitride ceramic and metal and the problem of how to reduce interface thermal resistance by realizing nano-thickness of the intermediate layer.
[0012] Preferably, the TiN transition layer has at least two layers, and as the number of the TiN transition layers increases, the nitrogen content is controlled to gradually decrease from 40% to 45% during the deposition of the TiN transition layers.
[0013] The present invention prepares TiN with a high nitrogen content by using nitrogen gas with a content of 40% to 45%, and then gradually reduces the nitrogen content in the TiN layer to transition from TiN to a pure Ti layer. The present invention realizes the transition from TiN to Ti by gradually reducing the nitrogen content in the TiN layer, so as to solve the problem of the interface bonding between silicon nitride ceramic and metal and the problem of how to reduce the interface thermal resistance.
[0014] Preferably, the process of depositing the TiN transition layer also includes controlling the nitrogen content to be 10% to 45%. The present invention controls the nitrogen content to adjust the thickness of the TiN transition layer and realizes the transition from TiN to Ti by gradually reducing the N content in the TiN layer.
[0015] Preferably, the method of depositing the TiN transition layer is:
[0016] Titanium target is used as target material, and the background vacuum degree is ≤5×10 -4 Pa, pass nitrogen, the nitrogen content is 10% to 45%, control the working pressure to 0.5Pa to 1.5Pa, the sputtering power is 2KW to 3KW, and the substrate bias is 50 to 70V; magnetron sputtering is performed to deposit a TiN transition layer on the surface of the ceramic substrate.
[0017] Preferably, the method of depositing the Ti transition layer is:
[0018] A titanium target is used as the target material, nitrogen is turned off, the working gas pressure is controlled to be 0.5Pa-1.5Pa, the sputtering power is 2KW-3KW, and the substrate bias is 50-70V; magnetron sputtering is performed to deposit a Ti transition layer on the surface of the Ti transition layer to form a TiN / Ti gradient transition layer.
[0019] Preferably, the method of depositing the Cu seed layer is:
[0020] A copper target is used as a target material, a working gas pressure is controlled at 0.5Pa-1.5Pa, and a sputtering power is controlled at 2KW-3KW; magnetron sputtering is performed to deposit a Cu seed layer on the surface of the TiN / Ti gradient transition layer.
[0021] Preferably, the thickness of the Cu seed layer is 5 μm to 10 μm. In the present invention, the thickness of the Cu seed layer can be selected according to actual needs.
[0022] Preferably, before depositing the TiN / Ti gradient transition layer, the process further includes: cleaning and drying the surface of the ceramic substrate; and performing glow sputtering cleaning on the ceramic substrate, thereby facilitating subsequent metallization treatment.
[0023] Preferably, the ceramic substrate is a silicon nitride ceramic substrate.
[0024] A second aspect of the present invention provides a ceramic copper-clad substrate, which is prepared by the metallization method of the ceramic substrate described in the first aspect.
[0025] Beneficial effects of the present invention:
[0026] 1. The present invention realizes reliable connection between the silicon nitride ceramic substrate and the metal copper by adding a TiN / Ti gradient transition layer between the ceramic substrate and the copper seed layer and controlling the thickness of the TiN / Ti gradient transition layer to nanometer, thereby greatly improving the interface bonding strength and cold and hot cycle resistance of the silicon nitride ceramic copper-clad substrate, so as to solve the problems that the existing metallization method of the silicon nitride ceramic substrate still has the problems of complex preparation process, large interface stress between the metal and ceramic resulting in poor interface bonding, and high thermal resistance of the multi-layer interface reducing the heat dissipation performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The X-ray diffraction patterns of the surface films of the ceramic copper-clad substrates prepared in Examples 1 to 3 are shown in Figures 1 to 3. (a) is the X-ray diffraction pattern of the surface film of the ceramic copper-clad substrate prepared in Example 1; (b) is the X-ray diffraction pattern of the surface film of the ceramic copper-clad substrate prepared in Example 2; (c) is the X-ray diffraction pattern of the surface film of the ceramic copper-clad substrate prepared in Example 3.
[0028] Figure 2 This is a cross-sectional morphology of the TiN film in the ceramic copper-clad substrate prepared in Example 3.
[0029] Figure 3 The surface morphology of the ceramic copper-clad substrate prepared in Examples 1 to 3 and Comparative Example 1 after 70 cycles of hot and cold cycles. Among them, (a) is a schematic diagram of the peeling of the transition layer system in Comparative Example 1 after thermal shock cycles; (b) is a schematic diagram of the peeling of the TiN / Ti gradient transition layer system in Example 1 after thermal shock cycle experiments; (c) is a schematic diagram of the peeling of the TiN / Ti gradient transition layer system in Example 2 after thermal shock cycle experiments; (d) is a schematic diagram of the peeling of the TiN / Ti gradient transition layer system in Example 3 after thermal shock cycle experiments; (e) is a partial enlarged schematic diagram of the peeling interface in (a); (f) is a partial enlarged schematic diagram of the peeling interface in (d). 1, 2, 3, 4, and 5 in (e) and (f) are different positions of the peeling interface, respectively. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0031] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0032] At present, the main metallization methods for silicon nitride ceramic substrates are direct copper coating and active metal brazing. The full name of direct copper coating is Direct Bond Copper, referred to as DBC. The full name of active metal brazing is Active Metal Brazing, referred to as AMB.
[0033] DBC technology refers to heating in oxygen-containing nitrogen at a high temperature of more than 1000°C, so that the copper foil and the ceramic substrate are firmly bonded together by eutectic bonding. It has high bonding strength, can weld thicker copper foils, such as 100μm to 600μm, and has good thermal conductivity and mechanical properties. It is widely used in IGBT module packaging of power devices. However, the preparation process temperature of DBC substrates is high, and the metal-ceramic interface stress is large, which limits the application of DBC substrates. Since micropores are easily generated between the ceramic and copper layers, the product's thermal shock resistance is reduced, which becomes a bottleneck for the application of DBC substrates in high power density and high reliability device packaging. In addition, the eutectic temperature and oxygen content of DBC substrates need to be strictly controlled during the preparation process, and high requirements are placed on equipment and process control, making its production cost relatively high.
[0034] AMB technology is a further development of DBC process technology. It mainly uses solder containing a small amount of active elements, such as Ti, Zr, etc., to chemically react with ceramics to generate a reaction layer on the ceramic surface, thereby improving the interfacial bonding between ceramics and metals. It is a widely used process for silicon nitride ceramic substrates. Silicon nitride substrates processed by AMB technology have high reliability. However, the AMB method is relatively expensive, there are fewer suitable active solders, and the solder composition and process have a greater impact on the welding quality. In practical applications, the thickness of the intermediate layer determines the welding quality. When the thickness is too thin, the intermediate layer is prone to discontinuity and defects such as holes, resulting in poor bonding. When the thickness is too thick, the large residual stress in the film layer can easily cause the substrate to crack and reduce the bonding strength; and due to the high thermal resistance of the multi-layer interface, the intermediate layer of tens to hundreds of microns thick in the AMB technology will reduce the heat dissipation performance to a certain extent.
[0035] Therefore, achieving precise nano-control of the thickness of the intermediate layer is an effective way to solve the two key problems of silicon nitride ceramic / metal interface bonding and reducing interface thermal resistance.
[0036] In summary, although the silicon nitride substrate processed by the above metallization method has a certain reliability, the existing metallization method of silicon nitride ceramic substrate still has the problems of complex preparation process, large interface stress between metal and ceramic resulting in poor interface bonding, and high thermal resistance of the multi-layer interface which reduces the heat dissipation performance.
[0037] In order to solve the above problems, the present invention proposes a method for realizing metallization of silicon nitride copper-clad substrate based on high-power pulsed magnetron sputtering technology, by adding a TiN / Ti gradient transition layer between the ceramic substrate and the copper seed layer, and controlling the thickness of the TiN / Ti gradient transition layer to nanometer, to achieve reliable connection between the silicon nitride ceramic substrate and the metal copper, greatly improve the interface bonding strength and cold and hot cycle resistance of the silicon nitride ceramic copper-clad substrate, so as to solve the problems that the existing metallization method of silicon nitride ceramic substrate still has complex preparation process, large interface stress between metal and ceramic resulting in poor interface bonding, and high thermal resistance of the multi-layer interface will reduce the heat dissipation performance.
[0038] The technical solution of the present invention is further described below by means of specific examples. In the following examples, the methods described are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0039] In the following embodiments, the purity of the Ti target and the Cu target is 99.99%; the purity of the argon gas and the nitrogen gas is 99.999%.
[0040] Example 1
[0041] A method for metallizing a ceramic substrate is to deposit a TiN / Ti gradient transition layer with a high nitrogen content on the surface of a silicon nitride substrate using a magnetron sputtering technique. The specific method comprises the following steps:
[0042] Step 1, cleaning of silicon nitride substrate: soak the silicon nitride substrate in anhydrous ethanol, ultrasonicate it in acetone and anhydrous ethanol for 10 to 15 minutes in sequence, and dry it.
[0043] Step 2: Glow cleaning: Install the dried silicon nitride substrate on the workpiece turntable in the vacuum chamber of the magnetron sputtering equipment, and install the Ti target and Cu target on the corresponding target positions. Then evacuate the vacuum chamber of the magnetron sputtering equipment to a pressure of ≤5×10 -4 After 300 Pa, argon gas is introduced to control the gas pressure to 0.5 Pa ~ 1.5 Pa, a bias voltage of -200 V ~ -500 V is applied to the silicon nitride substrate, and then glow cleaning is performed in a magnetron sputtering chamber for 30 min ~ 45 min.
[0044] Step 3, depositing a high nitrogen content TiN transition layer on the surface of the silicon nitride substrate: introducing argon and nitrogen with a purity of not less than 99.9%, a nitrogen content of 45%, a substrate bias of 60V, a working gas pressure of 0.8Pa, and a sputtering power of 2.5KW, and then depositing a 150nm high nitrogen content TiN transition layer on the surface of the silicon nitride substrate.
[0045] Step 4, depositing a Ti layer on the TiN transition layer: turn off the nitrogen, set the working gas pressure to 0.5 Pa, the substrate bias to 60 V, and the sputtering power to 2.5 KW, and deposit a 200 nm Ti layer on the high nitrogen content TiN transition layer.
[0046] Step 5, depositing a Cu seed layer on the high nitrogen content TiN / Ti gradient transition layer: turn on the Cu target, the working gas pressure is 0.5Pa, the Cu target sputtering power is 3KW, and a Cu seed layer with a thickness of 8μm is deposited on the high nitrogen content TiN / Ti gradient transition layer to prepare a ceramic copper-clad substrate with strong interface bonding.
[0047] In order to facilitate the subsequent thermal shock cycle experiment; the cut metal Cu foil was ultrasonically cleaned in acetone and anhydrous ethanol solution for 10 minutes respectively, and after drying, thick copper was coated on the Cu seed layer of the ceramic copper-clad substrate; the purpose of thick Cu coating is to conduct a thermal shock experiment to test the thermal cycle stability. Thick copper is metal Cu foil, and the thickness needs to reach 100μm-600μm. Then a hot and cold cycle experiment was performed in the temperature range of -10℃~150℃.
[0048] Example 2
[0049] A method for metallizing a ceramic substrate is to deposit a multi-layer TiN / Ti transition layer on the surface of a silicon nitride substrate using magnetron sputtering technology. The specific method includes the following steps:
[0050] Step 1, cleaning the silicon nitride ceramic plate: soaking the silicon nitride substrate in anhydrous ethanol, ultrasonicating it in acetone and anhydrous ethanol for 10 minutes to 15 minutes in sequence, and drying it.
[0051] Step 2: Glow cleaning: Install the dried silicon nitride substrate on the workpiece turntable in the vacuum chamber of the magnetron sputtering equipment, and install the Ti target and Cu target on the corresponding target positions. Then evacuate the vacuum chamber of the magnetron sputtering equipment to a pressure of ≤5×10 -4 After 300 Pa, argon gas is introduced to control the gas pressure to 0.5 Pa ~ 1.5 Pa, a bias voltage of -200 V ~ -500 V is applied to the silicon nitride substrate, and then glow cleaning is performed in a magnetron sputtering chamber for 30 min ~ 45 min.
[0052] Step 3, depositing two TiN transition layers on the surface of the silicon nitride substrate: introducing argon and nitrogen with a purity of not less than 99.9%, a nitrogen content of 45%, a substrate bias of 60V, a working gas pressure of 0.8Pa, and a sputtering power of 2.5KW, and depositing a 100nm high nitrogen content TiN transition layer on the surface of the silicon nitride substrate; reducing the nitrogen content to 20%, the substrate bias of 60V, the working gas pressure of 0.6Pa, and the sputtering power of 2.5KW, and depositing a 100nm low nitrogen content TiN transition layer.
[0053] Step 4, depositing a Ti layer on the two TiN transition layers: turn off the nitrogen, set the working gas pressure to 0.5 Pa, the substrate bias to 60 V, and the sputtering power to 2.5 KW, and deposit a 200 nm Ti layer on the two TiN transition layers.
[0054] Step 5, depositing a Cu seed layer on the multilayer TiN / Ti transition layer: turn on the Cu target, the working gas pressure is 0.5Pa, the Cu target sputtering power is 2.5KW, and a Cu seed layer with a thickness of 8μm is deposited on the multilayer TiN / Ti transition layer to prepare a ceramic copper-clad substrate with strong interface bonding.
[0055] In order to facilitate the subsequent thermal shock cycle experiment; the cut metal Cu foil was ultrasonically cleaned in acetone and anhydrous ethanol solution for 10 minutes respectively, and after drying, thick copper was coated on the Cu seed layer of the ceramic copper-clad substrate; the purpose of thick Cu coating is to conduct a thermal shock experiment to test the thermal cycle stability. Thick copper is metal Cu foil, and the thickness needs to reach 100μm-600μm. Then a hot and cold cycle experiment was performed in the temperature range of -10℃~150℃.
[0056] Example 3
[0057] A method for metallizing a ceramic substrate is to deposit a multi-layer TiN / Ti transition layer on the surface of a silicon nitride substrate using magnetron sputtering technology. The specific method includes the following steps:
[0058] Step 1, cleaning the silicon nitride ceramic plate: ultrasonically cleaning the silicon nitride substrate with acetone, anhydrous ethanol, and deionized water for 10 minutes in sequence, and drying.
[0059] Step 2: Glow cleaning: Install the dried silicon nitride substrate on the workpiece turntable in the vacuum chamber of the magnetron sputtering equipment, and install the Ti target and Cu target on the corresponding target positions. Then evacuate the vacuum chamber of the magnetron sputtering equipment to a pressure below 5×10 -4 After 300 Pa, argon gas is introduced to control the gas pressure to 0.5 Pa ~ 1.5 Pa, a bias voltage of -200 V ~ -500 V is applied to the silicon nitride substrate, and then glow cleaning is performed in a magnetron sputtering chamber for 30 min ~ 45 min.
[0060] Step 3, depositing a multilayer TiN transition layer on the surface of the silicon nitride substrate: depositing a TiN base layer on the silicon nitride substrate, with a sputtering power of 3KW, a substrate bias of 70V, a nitrogen content of 45%, a deposition thickness of 100nm, and a background vacuum of no more than 5×10 -4 Pa, working pressure 1.0-1.5Pa; then the nitrogen content is reduced to 35%, the working pressure is 1.0Pa, and a TiN transition layer with a thickness of 150nm is deposited; finally, the nitrogen content is reduced to 10%, the working pressure is 0.3Pa, and a low nitrogen content TiN transition layer with a thickness of 200nm is deposited.
[0061] Step 4, depositing a Ti layer on the multi-layer TiN transition layer: turn off the nitrogen, control the gas pressure to 1.5 Pa, deposit Ti on the transition layer, sputtering power 3 KW, substrate bias 70 V, and the deposited Ti layer thickness is 200 nm.
[0062] Step 5, depositing a Cu seed layer on the multilayer TiN / Ti transition layer: turning on the Cu target, controlling the gas pressure to 1.5 Pa, the Cu target sputtering power to 3 KW, depositing a Cu seed layer with a thickness of 10 μm, and preparing a ceramic copper-clad substrate with strong interface bonding.
[0063] Comparative Example 1
[0064] A method for metallizing a ceramic substrate is to deposit a Ti transition layer on the surface of a silicon nitride substrate using a magnetron sputtering technique. The specific method comprises the following steps:
[0065] Step 1, cleaning the silicon nitride ceramic plate: ultrasonically cleaning the silicon nitride substrate with acetone, anhydrous ethanol, and deionized water for 10 minutes in sequence, and drying.
[0066] Step 2: Glow cleaning: Install the dried silicon nitride substrate on the workpiece turntable in the vacuum chamber of the magnetron sputtering equipment, and install the Ti target and Cu target on the corresponding target positions. Then evacuate the vacuum chamber of the magnetron sputtering equipment to a pressure below 5×10 -4 After 300 Pa, argon gas is introduced to control the gas pressure to 0.5 Pa ~ 1.5 Pa, a bias voltage of -200 V ~ -500 V is applied to the silicon nitride substrate, and then glow cleaning is performed in a magnetron sputtering chamber for 30 min ~ 45 min.
[0067] Step 3: Deposit a Ti transition layer on the surface of the silicon nitride substrate: Keep the nitrogen closed and the background vacuum no higher than 5×10 - 4 Pa, the gas pressure was controlled at 1.5 Pa, a Ti transition layer was deposited on the surface of the silicon nitride substrate, the sputtering power was 3 KW, the substrate bias was 70 V, and the thickness of the deposited Ti layer was 200 nm.
[0068] Step 4, depositing a Cu seed layer on the Ti transition layer: turning on the Cu target, controlling the gas pressure to 1.5 Pa, the Cu target sputtering power to 3 KW, depositing a Cu seed layer with a thickness of 10 μm, and preparing a ceramic copper-clad substrate with strong interface bonding.
[0069] In order to facilitate the subsequent thermal shock cycle experiment; the cut metal Cu foil was ultrasonically cleaned in acetone and anhydrous ethanol solution for 10 minutes respectively, and after drying, thick copper was coated on the Cu seed layer of the ceramic copper-clad substrate; the purpose of thick Cu coating is to conduct a thermal shock experiment to test the thermal cycle stability. Thick copper is metal Cu foil, and the thickness needs to reach 100μm-600μm. Then a hot and cold cycle experiment was performed in the temperature range of -10℃~150℃.
[0070] Table 1 Magnetron sputtering conditions of TiN transition layer
[0071]
[0072] Table 2 Thickness of different sputtered layers
[0073]
[0074]
[0075] Test 1: X-ray diffraction analysis.
[0076] X-ray diffraction analysis was performed on the surface films of the ceramic copper-clad substrates prepared in Examples 1 to 3. The results are shown in Figure 1 .
[0077] Figure 1 The X-ray diffraction patterns of the surface films of the ceramic copper-clad substrates prepared in Examples 1 to 3 are shown in Figures 1 to 3. (a) is the X-ray diffraction pattern of the surface film of the ceramic copper-clad substrate prepared in Example 1; (b) is the X-ray diffraction pattern of the surface film of the ceramic copper-clad substrate prepared in Example 2; (c) is the X-ray diffraction pattern of the surface film of the ceramic copper-clad substrate prepared in Example 3.
[0078] Depend on Figure 1 It can be seen from the results that the surface films of the ceramic copper-clad substrates prepared in Examples 1 to 3 all contain Si3N4, Ti2N, Ti3N4, Ti, Cu3Ti and Cu.
[0079] Test 2: Cross-sectional morphology analysis.
[0080] The cross-sectional morphology of the TiN film in the ceramic copper-clad substrate prepared in Example 3 was analyzed. Figure 2 . Figure 2 This is a cross-sectional morphology of the TiN film in the ceramic copper-clad substrate prepared in Example 3.
[0081] There is no obvious difference in the cross-sectional morphology of Examples 1 and 2 from that of Example 3.
[0082] Depend on Figure 2The results show that the TiN film deposited in Example 3 has a dense structure and fine grain structure. There is no gap between the film and the silicon nitride substrate, and there are no undulations on the surface of the film, and there are no defects such as holes at the interface.
[0083] Test 3: Thermal shock cycle experiment.
[0084] The ceramic copper-clad substrate prepared in Example 3 was subjected to a thermal cycle test in the temperature range of -10°C to 150°C, and the peeling condition after 70 cycles of thermal cycles was observed. The results are shown in Figure 3 .
[0085] Table 3 Compositions at different positions of the peeling interface in Comparative Example 1 (at.%)
[0086] element 1 2 3 4 5 Si 0.04 0.32 89.46 96.86 96.17 Ti 0.79 0.00 10.54 0.23 0.52 Cr 11.30 2.09 0.00 0.00 0.00 Cu 87.87 97.60 0.00 2.91 3.32
[0087] Table 4 Compositions at different positions of the peeling interface in Example 3 (at.%)
[0088] element 1 2 3 4 5 Si 99.69 99.66 93.99 96.37 0.42 Ti 0.34 0.00 2.26 0.00 0.00 Cr 0.00 0.06 0.50 0.00 1.04 Cu 0.00 0.28 3.26 3.63 98.54
[0089] Figure 3 The surface morphology of the ceramic copper-clad substrate prepared in Examples 1 to 3 and Comparative Example 1 after 70 cycles of hot and cold cycles. Among them, (a) is a schematic diagram of the peeling of the transition layer system in Comparative Example 1 after thermal shock cycles; (b) is a schematic diagram of the peeling of the TiN / Ti gradient transition layer system in Example 1 after thermal shock cycle experiments; (c) is a schematic diagram of the peeling of the TiN / Ti gradient transition layer system in Example 2 after thermal shock cycle experiments; (d) is a schematic diagram of the peeling of the TiN / Ti gradient transition layer system in Example 3 after thermal shock cycle experiments; (e) is a partial enlarged schematic diagram of the peeling interface in (a); (f) is a partial enlarged schematic diagram of the peeling interface in (d). 1, 2, 3, 4, and 5 in (e) and (f) are different positions of the peeling interface, respectively.
[0090] Depend on Figure 3 The results show that the thermal fatigue performance of the TiN / Ti gradient transition layer system in Examples 1 to 3 is better than that of the pure Ti system in Comparative Example 1, and the thermal fatigue performance of the TiN / Ti gradient transition layer system in Example 3 is the best.
[0091] According to the composition analysis of different positions of the peeling interface in Tables 3 and 4, it can be seen that the peeling interface is between the transition layer and the Si3N4 substrate, which proves that the core of enhancing the ceramic metallization bonding strength of Example 3 lies in improving the bonding strength between the TiN / Ti gradient transition layer and the Si3N4 substrate, and at the same time verifies the superiority of the TiN / Ti gradient transition layer.
[0092] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for metallizing a ceramic substrate, characterized in that: The following steps are involved: A TiN / Ti gradient transition layer and a Cu seed layer are sequentially deposited on the surface of a ceramic substrate by a magnetron sputtering method to prepare a ceramic copper-clad substrate; The TiN / Ti gradient transition layer comprises a TiN transition layer and a Ti transition layer; the thickness of the TiN transition layer is between 100nm and 600nm; the thickness of the Ti transition layer is between 100nm and 200nm.
2. The method for metallizing a ceramic substrate according to claim 1, characterized in that: The TiN transition layer has at least one layer, and the thickness of each TiN transition layer is between 100nm and 200nm.
3. The method for metallizing a ceramic substrate according to claim 2, characterized in that: The TiN transition layer has at least two layers, and as the number of the TiN transition layers increases, the nitrogen content is controlled to gradually decrease from 40% to 45% during the deposition of the TiN transition layers.
4. The method for metallizing a ceramic substrate according to claim 1, characterized in that: The method for depositing the TiN transition layer is: Titanium target is used as target material, and the background vacuum degree is ≤5×10 -4 Pa, pass nitrogen, the nitrogen content is 10% to 45%, control the working pressure to 0.5Pa to 1.5Pa, the sputtering power is 2KW to 3KW, and the substrate bias is 50 to 70V; magnetron sputtering is performed to deposit a TiN transition layer on the surface of the ceramic substrate.
5. The method for metallizing a ceramic substrate according to claim 1, characterized in that: The method of depositing the Ti transition layer is: A titanium target is used as the target material, nitrogen is turned off, the working gas pressure is controlled to be 0.5Pa-1.5Pa, the sputtering power is 2KW-3KW, and the substrate bias is 50-70V; magnetron sputtering is performed to deposit a Ti transition layer on the surface of the Ti transition layer to form a TiN / Ti gradient transition layer.
6. The method for metallizing a ceramic substrate according to claim 1, characterized in that: The method for depositing the Cu seed layer is: A copper target is used as a target material, a working gas pressure is controlled at 0.5Pa-1.5Pa, and a sputtering power is controlled at 2KW-3KW; magnetron sputtering is performed to deposit a Cu seed layer on the surface of the TiN / Ti gradient transition layer.
7. The method for metallizing a ceramic substrate according to claim 1, characterized in that: The Cu seed layer has a thickness of 5 μm to 10 μm.
8. The method for metallizing a ceramic substrate according to claim 1, characterized in that: Before depositing the TiN / Ti gradient transition layer, the method further includes: cleaning and drying the surface of the ceramic substrate; and performing glow sputtering cleaning on the ceramic substrate.
9. The method for metallizing a ceramic substrate according to claim 1, characterized in that: The ceramic substrate is a silicon nitride ceramic substrate.
10. A ceramic copper-clad substrate, characterized in that: The ceramic substrate is prepared by the metallization method of claim 1.
Citation Information
Patent Citations
Titanium alloy surface nano Ti / TiN gradient film and preparation method thereof
CN104862657A
Surface metallization method for high-thermal-conductivity silicon nitride ceramic substrate and packaging substrate thereof
CN111192831A
Silicon nitride ceramic substrate solid lubrication film, preparation method and preparation system
CN118422124A
Copper / ceramic assembly, insulating circuit substrate, production method for copper / ceramic assembly, and production method for insulating circuit substrate
US20240274497A1
Cited By
Ceramic substrate laser powder bed molten metal structure based on multiple transition layers and preparation method of ceramic substrate laser powder bed molten metal structure
CN121610794A